2022
DOI: 10.3390/ijerph19042101
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Experience of End-of-Life Stage Elderly Patients: Longitudinal Qualitative Interview

Abstract: Objectives: This study seeks to provide an understanding of the changing experiences in caregivers of end-of-life patients in Hong Kong through exploring their caregiving journey. Methods: Using longitudinal individual qualitative interviews, a total of 14 caregivers of community-dwelling elderly patients receiving end-of-life care were recruited between 2015 and 2016. A series of in-depth interviews and observations were conducted in 14 cases during the end-of-life journey. Results: A thematic analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…33 On a similar note, Wong, et al reported that end-stage patients suffer from severe depression and have suicidal thoughts; caregivers can provide these patients with emotional and mental support to reduce their depression and help them manage their psychological tension. 34 Dealing with their feelings of shame and guilt is a major contributory factor in managing psychological tension in patients who attempted suicide. After their suicide attempt, many of these patients feel ashamed and guilty about the grave anxiety and concern they created in their families.…”
Section: Discussionmentioning
confidence: 99%
“…33 On a similar note, Wong, et al reported that end-stage patients suffer from severe depression and have suicidal thoughts; caregivers can provide these patients with emotional and mental support to reduce their depression and help them manage their psychological tension. 34 Dealing with their feelings of shame and guilt is a major contributory factor in managing psychological tension in patients who attempted suicide. After their suicide attempt, many of these patients feel ashamed and guilty about the grave anxiety and concern they created in their families.…”
Section: Discussionmentioning
confidence: 99%
“…(38) The use of longitudinal data, which tracks practices, perspectives, individual relevancies, and experiences over time, offers signi cant bene ts in various research elds, including life course, social policy, health, migration, and family research. (39) Longitudinal qualitative research on caregivers and vulnerable people has been conducted in the past (40)(41)(42)(43)(44)(45) this method in the eld of disability has a signi cant strength in illustrating the impact of environmental or contextual factors on participants' experiences as they unfold over time. (46) Research demonstrated to gain a comprehensive understanding of how politics and policies affect the opportunities and choices available to individuals, it is necessary to observe and track their experiences over an extended period of time.…”
Section: Research Design and Settingsmentioning
confidence: 99%
“…Level of stress (cause Prateepataam) associated with end-of-life care management (Pretakriti) varies according to the progression of the illness. 79 The word Pretakriti denotes a dying patient showing features such as severe weakness, multiple organ failure, reduced ability, mobility, oral intake, cognitive function, alertness and communication, increased periods of sleep etc. Hence Preshya Prateepataam Yanti Pretakriti denotes caregiver burden/stress in informal caregivers providing endof-life care management.…”
Section: Mattavadgati --Vedanaam (Verse 25)mentioning
confidence: 99%